2017
DOI: 10.1080/08869634.2017.1298226
|View full text |Cite
|
Sign up to set email alerts
|

Cervical posture analysis in dental students and its correlation with temporomandibular disorder

Abstract: It can be concluded, therefore, that no relationship exists between cervical posture in the sagittal plane and TMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 16 publications
0
18
0
1
Order By: Relevance
“…A magnetic resonance imaging study observed that disc displacement was not related to hyoid bone position [ 14 ]. Câmara-Souza et al observed no relationship between TMD and hyoid bone position in 80 dental students [ 19 ]. Ekici and Camci reported that the hyoid bone in patients with TMD was located closer to the cranium [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…A magnetic resonance imaging study observed that disc displacement was not related to hyoid bone position [ 14 ]. Câmara-Souza et al observed no relationship between TMD and hyoid bone position in 80 dental students [ 19 ]. Ekici and Camci reported that the hyoid bone in patients with TMD was located closer to the cranium [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diferente dos achados do atual estudo, outros autores relatam não encontrar diferenças na postura craniocervical entre indivíduos com e sem DTM. Sugerem que as alterações posturais estejam mais relacionadas à ocorrência de distúrbios craniocervicais, ou que os aspectos psicossociais podem ter influências sobre os principais sintomas das desordens e do quadro álgico, não sendo possível determinar se os desvios posturais são a causa ou o resultado da desordem (ARMIJO-OLIVO et al, 2011;CÂMARA-SOUZA et al, 2018;MATHEUS et al, 2009;SAI-TO;AKASHI;SACCO, 2009). Comparando as posturas craniocervicais com as classes de oclusão dentaria demonstrados na tabela 3, pôde-se constatar que estes dados estão de acordo com a literatura que afirma ter a posteriorização da cabeça maior prevalência na subclasse IIa (BIASOTTO-GONZALEZ et al, 2008).…”
Section: Discussionunclassified
“…Temporomandibular disorder (TMD) refers to a group of conditions that compromise the harmonious movement and function of the temporomandibular joint (TMJ), masticatory muscles, and associated structures. 1 Chronic TMD commonly occurs as orofacial pain, and is considered a public health problem. 2 It occurs more frequently and severely in women than in men.…”
Section: Introductionmentioning
confidence: 99%